Voice to Parliament article series - Andrea Carson; Max Grömping; Simon Jackman; Rebecca Strating; Justin Phillips (2023)
The six-part series of The Conversation articles was part of a Voice to Parliament referendum research project that used cutting edge big data and methods to understand who shaped the debate and with what messages. The articles were as follows: August 30, 2023, Andrea Carson, Max Grömping and Simon Jackman 'Voice referendum: is the ‘yes’ or ‘no’ camp winning on social media, advertising spend and in the polls?' https://theconversation.com/voice-referendum-is-the-yes-or-no-camp-winning-on-social-media-advertising-spend-and-in-the-polls-208956 September 12, 2023, Andrea Carson, Rebecca Strating and Simon Jackman 'The ‘no’ campaign is dominating the messaging on the Voice referendum on TikTok – here’s why' https://theconversation.com/the-no-campaign-is-dominating-the-messaging-on-the-voice-referendum-on-tiktok-heres-why-212465 September 26, 2023, Andrea Carson, Max Grömping, Rebecca Strating and Simon Jackman ‘The ‘yes’ Voice campaign is far outspending ‘no’ in online advertising, but is the message getting through?’ https://theconversation.com/the-yes-voice-campaign-is-far-outspending-no-in-online-advertising-but-is-the-message-getting-through-213749 October 4, 2023, Rebecca Strating, Andrea Carson, Simon Jackman ‘How might the First Nations Voice to Parliament referendum affect Australia’s international reputation?’ https://theconversation.com/how-might-the-first-nations-voice-to-parliament-referendum-affect-australias-international-reputation-213764 October 11, 2023, Andrea Carson, Justin Phillips, Max Grömping, Rebecca Strating and Simon Jackman 'The ‘yes’ campaign is generating the most media and social media content. Yet, it continues to trail in the polls' https://theconversation.com/the-yes-campaign-is-generating-the-most-media-and-social-media-content-yet-it-continues-to-trail-in-the-polls-215145 October 15, 2023, Rebecca Strating and Andrea Carson '‘Lies fuel racism’: how the global media covered Australia’s Voice to Parliament referendum' ...